Behavioural public administration: a systematic review on the effects of cognitive biases on public adminstration decisions - Iwasa, Fabio Takeji; de Almeida, Fernando Carvalho (Revista Expectativa, 2021)
Public administration and psychology can dialogue by outlining a distinct approach in public administration that integrates both fields of study: behavioral public administration. The behavioral public administration can be beneficial for practitioners, such as policy makers, public managers, and public professionals, by the development of usable knowledge. This paper aims to elaborate a systematic literature review of the findings on the application of the behavioral economics principles on the public administration and the effects of cognitive biases from the behavioral economics perspectives on public managerial decisions. It will provide a comprehensive overview of the problems that could emerge from this decision-making process. The main contribution that is objected through this research is consolidate the current state of the art on the cognitive biases studies within Public Administration and identify the application and theoretical knowledge gaps that can provide new research opportunities. RESUMO A administração pública e a psicologia podem dialogar delineando uma abordagem distinta na administração pública que integra os dois campos de estudo: administração pública comportamental. A administração pública comportamental pode ser benéfica para os profissionais, como formuladores de políticas, gestores públicos e profissionais públicos, pelo desenvolvimento de conhecimento utilizável. Este artigo tem como objetivo elaborar uma revisão sistemática da literatura dos achados sobre a aplicação dos princípios da economia comportamental na administração pública e os efeitos dos vieses cognitivos da perspectiva da economia comportamental nas decisões gerenciais públicas. Ele fornecerá uma visão abrangente dos problemas que podem surgir desse processo de tomada de decisão. A principal contribuição que se objetiva com esta pesquisa é consolidar o estado da arte atual sobre os estudos de vieses cognitivos na Administração Pública e identificar as lacunas de aplicação e de conhecimento teórico que podem proporcionar novas oportunidades de pesquisa.